Microbial communities with distinct denitrification potential in spruce and beech soils differing in nitrate leaching - Bárta, Jiří; Tahovská, Karolina; Šantrůčková, Hana; Oulehle, Filip (Scientific reports, 2017)
Nitrogen leaching owing to elevated acid deposition remains the main ecosystem threat worldwide. We aimed to contribute to the understanding of the highly variable nitrate losses observed in Europe after acid deposition retreat. Our study proceeded in adjacent beech and spruce forests undergoing acidification recovery and differing in nitrate leaching. We reconstructed soil microbial functional characteristics connected with nitrogen and carbon cycling based on community composition. Our results showed that in the more acidic spruce soil with high carbon content, where Acidobacteria and Actinobacteria were abundant (Proteo:Acido = 1.3), the potential for nitrate reduction and loss via denitrification was high (denitrification: dissimilative nitrogen reduction to ammonium (DNRA) = 3). In the less acidic beech stand with low carbon content, but high nitrogen availability, Proteobacteria were more abundant (Proteo:Acido = 1.6). Proportionally less nitrate could be denitrified there (denitrification:DNRA = 1), possibly increasing its availability. Among 10 potential keystone species, microbes capable of DNRA were identified in the beech soil while instead denitrifiers dominated in the spruce soil. In spite of the former acid deposition impact, distinct microbial functional guilds developed under different vegetational dominance, resulting in different N immobilization potentials, possibly influencing the ecosystem's nitrogen retention ability.
Keywords: Picea; dusičnany; mikrobiota; půda; Microbiota; Europe; denitrifikace; buk (rod); půdní mikrobiologie; Nitrates; Hydrogen-Ion Concentration; Denitrification; Bacteria; Soil; smrk; koncentrace vodíkových iontů; Fagus; Evropa; Soil Microbiology